2012
DOI: 10.1038/ncb2632
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax toxin receptor 2a controls mitotic spindle positioning

Abstract: Oriented mitosis is essential during tissue morphogenesis. The Wnt/planar cell polarity (Wnt/PCP) pathway orients mitosis in a number of developmental systems, including dorsal epiblast cell divisions along the animal-vegetal (A-V) axis during zebrafish gastrulation. How Wnt signalling orients the mitotic plane is, however, unknown. Here we show that, in dorsal epiblast cells, anthrax toxin receptor 2a (Antxr2a) accumulates in a polarized cortical cap, which is aligned with the embryonic A-V axis and forecasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 57 publications
3
59
0
Order By: Relevance
“…Published experiments by others aimed at detecting interaction between highly overexpressed CMG2 and actin have yielded disparate results (10,53,54). In cells expressing a native amount of CMG2, we found that the addition of PA promotes the association of the toxin/receptor complex with actin cytoskeleton fractions that remain insoluble and sediment rapidly in preparations treated with the nonionic detergent Triton X-100 (54-56), facilitating endocytosis of both PA and CMG2 (Fig.…”
Section: Effect Of Pharmacological Inhibition Of Calpain On Anthrax Tmentioning
confidence: 74%
“…Published experiments by others aimed at detecting interaction between highly overexpressed CMG2 and actin have yielded disparate results (10,53,54). In cells expressing a native amount of CMG2, we found that the addition of PA promotes the association of the toxin/receptor complex with actin cytoskeleton fractions that remain insoluble and sediment rapidly in preparations treated with the nonionic detergent Triton X-100 (54-56), facilitating endocytosis of both PA and CMG2 (Fig.…”
Section: Effect Of Pharmacological Inhibition Of Calpain On Anthrax Tmentioning
confidence: 74%
“…The loss of basal actin cables (also known as stress fibres) is likely to be a direct consequence of the disassembly of cell-substrate adhesions 13 . There is also a shift in the dominance of different cortical actin nucleators at the onset of mitosis, from the ARP2/3 complex to formins 14,35,36 . For cells enter ing mitosis in culture, this is apparent from the loss of lamellipodia, which are actinbased membrane pro trusions that are generated by branched actin filament nucleation downstream of Rac, the SCAR/WAVE com plex [37][38][39] and the ARP2/3 complex.…”
Section: Adherens Junctionsmentioning
confidence: 99%
“…For cells enter ing mitosis in culture, this is apparent from the loss of lamellipodia, which are actinbased membrane pro trusions that are generated by branched actin filament nucleation downstream of Rac, the SCAR/WAVE com plex [37][38][39] and the ARP2/3 complex. Although the extent to which residual ARP2/3 activity contributes to the gener ation of mitotic structures is currently unclear 14,35,36 , this loss of lamellipodial actin is accompan ied by the activ ation of the forminbased actin nucleator Diaphanous (DIA) 14 , which drives the assembly of a cortical net work of actin filaments. Importantly, once activated, through physical association with Rhofamily GTPases, DIA gener ates nonbranched actin filaments.…”
Section: Adherens Junctionsmentioning
confidence: 99%
“…Very recent studies of the Antxr2 receptor during oriented divisions of zebrafish epiblasts have also identified a necessary role for Dia, although it remains uncertain whether Antxr2a-mediated spindle orientation is strictly dependent on actin nucleation (Castanon et al, 2013). Interestingly, Dsh-mediated actin nucleation is required for Antxr2 cortical localization, although actin polymerization is regulated by ROK downstream of Dsh in this system.…”
Section: Resultsmentioning
confidence: 93%